Analisis densitas Zooxanthella pada karang Acropora sp di Perairan Pulau Talam Tapanuli Tengah Provinsi Sumatera Utara - Novri Ditama Syafni; Thamrin Thamrin; Efriyeldi Efriyeldi (Pelantar Press, 2022)
Coral reefs are a unique ecosystem of tropical waters that have physical function as a beach protector with its nature that can reduce the energy of waves moving towards the coast. Coral reef ecosystems are a good places for spawning, nurturing and food sources for fish. The aim of this research was to determine the density of zooxanthella on coral Acropora sp based on different depths. The method that used in this research was a survey method by taking coral samples using purposive sampling technique, then the samples were analyzed and the data was discussed descriptively at the Marine Biology Laboratory, Faculty of Fisheries and Marine, Riau University. The results of this research on the waters of Talam Island obtained a brightness up to 100% of depth, a current velocity was 0.05–0.10 m/s, temperature ranging from 30-32 0C, salinity of 34 o/oo and pH ranging from 7.2–7.6. The corals that used as research objects for zooxanthella density were taken at a depth of 3 m, 5 m, and 7 m, namely the coral Acropora sp. The results showed that the average zooxanthella density on Acropora sp coral at a depth of 3 meters was 6.35x106 cells/cm2, a depth of 5 meters was 2.63x106 cells/cm2, and 1.95x106 cells/cm2 at a depth of 7 meters. Based on observations, the density zooxanthella was decreased by increasing depth.